以马內利中专二校会计三年级学生对汉语阅读技能与兴趣的掌握情况 - Se Lin; Ina Ina; Suhardi Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractReading is one of the important aspects, reading can obtain information and knowledge and can improve understanding. If students have good reading interests and abilities, it is not difficult for students to take mandarin lessons. So that students can take Mandarin lessons well, te authors carry out an ability test method and a reading interest survey to 12th grade accounting students of Immanuel vocational high school. This research is divided into three parts. First, the researcher gave the HSK test, it was found that 49% of the students had completed and 51% of the students had not finished. In the second test, namely the reading test method with and without pinyin, it was found that the reading test without pinyin was 51% of students completed and the reading test with pinyin was 73% of students completed. Based on the results of the student's reading ability test, it can be said that the students' reading ability is still lacking and needs to be improved. The survey results found that as many as 4% of students really like reading, 39% of students like reading, 49% of students don't like reading and 8% of students really don't like reading. Lack of interest in reading in 12th grade accounting students of Immanuel vocational high school, namely students are not active in reading activities and students prefer other activities than reading.Keywords: Reading, Interest, Ability